Experience of Dementia-related Anxiety in Middle-aged Female Caregivers for Family Members with Dementia: A Phenomenological Study - Jeong Sun Kim, RN, PhD; Eun Ha Kim, RN, PhD; Minjeong An, PhD, RN, FNP-BC (Elsevier, 2016)
Purpose: In Korea, most elderly with dementia receive care from family members, yet little research is available on the experience of dementia-related anxiety in middle-aged female caregivers for a family member with dementia. The purpose of this study was to describe the lived experience of dementia-related anxiety in middle-aged female caregivers for family members with dementia. Methods: A descriptive phenomenological study was conducted. A purposive sampling strategy was used to recruit participants. Twelve middle-aged women (40-59 years, mean age = 51.90 years) who were family caregivers were interviewed from February 2014 to August 2014. Data were collected through semistructured interviews and analyzed using Giorgi's method. Results: The essential structure of the phenomenon was a fear of losing self-identity. The main essence was represented by six components: keenly feeling the effects of aging because of memory deficit, continuous comparison of the family member's behavior with that of the participant's, Finding it painful to see a family member with dementia as he/she does not know how this will end, not knowing the conclusion of the disease process, reducing the risk of dementia, and trying to change one's lifestyle from what it used to be in the past. Conclusions: The study provides the essential structure of the experience on dementia-related anxiety that caregivers of a family member with dementia have. The findings could help healthcare providers and researchers have better understanding of dementia-related anxiety and give more attention to the caregivers to relieve their anxiety.